Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) terhadap Hasil Belajar Matematika Siswa Kelas IV SD Katolik Bali Loura - Ni Nyoman Trisnawati; Yohana Anggreni Talo; Imakulata Magi Loda (Indo-MathEdu Intellectuals Journal, 2026)
The problem in this study is the low mathematics learning outcomes of students, with an average score of 66.5 with only 37.5% of students achieving the minimum mastery criteria. This study aims to determine the effect of the Student Teams Achievement Division (STAD) cooperative learning model on the mathematics learning outcomes of fourth-grade students at SD Katolik Bali Loura. This study employed a quasi-experimental method with a non-equivalent control group design. The sample consisted of 48 students, divided into 24 students in the experimental class and 24 students in the control class. Data were collected through pretest and posttest and analyzed using N-Gain and independent sample t-test. The results showed a significant improvement in learning outcomes, with a significance value of 0.000 < 0.05. This indicates that the STAD cooperative learning model has a significant effect on students mathematics learning outcomes. This study is limited to the cognitive domain, therefore future research is recommended to examine affective and psychomotor aspects in order to obtain more comprehensive results.